Características del trastorno de ansiedad social o fobia social en el adolescente - Alccalaico Mamani, Marina (2019)
The aim of this paper is to raise awareness about the features of social anxiety disorder or social phobia showing thelimitations that result in different fields of cognitive behavioral area and help to disseminate information awakeningnew motivations to his profound study, the development of programs and management techniques for preventionand treatment to a maximum level of anxiety, it will be very useful for those with anxiety, for those working inresearch and treatment for needy readers. For this paper, the concepts of social phobia, the ontological nature ofanxiety, anxiety subtypes, background denoting the importance of their study, the effects of anxiety. It also showsthe size of the system and finally cognitive behavioral conditions are factors why it occurs. We conclude that SocialAnxiety Disorder is negatively related to personal development in various fields of human beings.